PENENTUAN BILANGAN REYNOLD DAN FROUDE, REDESIGN ZONA SEDIMENTASI RECTANGULAR DENGAN PLATE SETTLER DAN TUBE SETTLER, WATER TREATMENT PLANT (WTP), KAWASAN INDUSTRI DAN PERUMAHAN “X”, KABUPATEN BEKASI - Aris Dwi Cahyanto; Ilyas Nur Ilman; Armen Putra (Jurnal Poli-Teknologi, 2023)
Sedimentation is the separation between solids and solutions with the force of gravity. To improve the performance and efficiency of sedimentation tanks, it can be done by adding a device, namely pseudo base, plate settler, or tube settler. The purpose of this study is to modify rectangular sedimentation zones with plate settlers and tube settlers in the Water Treatment Plant (WTP) and analyze the flow that occurs in the sedimentation zone by examining Reynold numbers (NRE) and Froude numbers (NFR). To achieve this goal, the authors conducted field observations on the sedimentation unit in the Industrial Water Treatment Plant and "X" residential area of Bekasi Regency. The results obtained are the optimal type of tube settler, hexagon cross section tube settler using the height of the tube settler (Htube) 2.5 meters, the slope angle of the tube settler (α) 30°, and the diameter of the tube settler (w) 0.05 meters. Increased discharge from the initial capacity of 170 lps to 510 lps resulted in changes in flow conditions that occur. Changes in flow from turbulent to laminer are indicated by changes in Reynold numbers (NRE) from over 2000 to less than 2000, and Froude (NFR) numbers have met the design criteria of less than 10-5. The investment cost for adding a tube settler is Rp. 760,000,000.00 with a return on investment or a Payback Period (PP) for 8,38 years. The Reynold number (NRE) indicates the type of flow that occurs is laminer, transition, or turbulent. While the Froude number (NFR) indicates the type of flow whether a short flow occurs or not. For field application, the tube settler that can be used is to consider the height aspect of the tube settler (Htube), the slope angle of the tube settler (α), and the diameter of the tube settler (w), and the type of cross section of the tube settler